CYBERMUSEOLOGY AND INTANGIBLE HERITAGE - Langlais, Dominique (eTopia, 2005)
In the globalization process many cultural traditions around the world tend to disappear under the pressure of standardisation of practice and content. Cultural diversity seems to recede more and more. In a proactive position, UNESCO made a universal declaration on cultural diversity in 2001 that it would aim at heritage preservation.In the same effort of protection and enhancement of cultural diversity, museums are developing Internet material to preserve and disseminate cultural knowledge and heritage and to create interactive experiences between users and content. This has given birth to what some refer to as cybermuseology. But one can ask, do virtual museums present more than images of objects? Can the knowledge of localised cultural heritage and practices be transferred without losing the context it stems from, or what de B’béri (Cinema andSocial Discourse 64) defines as “the condition under which a society produces specific meaning”? More specifically, can information and communication technologies (ICT) transfer tacit knowledge, human experience, and tangible cultural heritage, and if so, what can we learn through this new process of cultural codification?This paper shall focus on explaining cybermuseology and then explore the process of knowledge codification and the links we can draw with heritage codification. In the last section I will discuss virtual experiences and try to determine how museums are using the virtual to protect and promote cultural diversity.